2016
DOI: 10.3390/ma9120971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hot Plastic Deformation in γ and (γ + α) Area on the Structure and Mechanical Properties of High-Strength Low-Alloy (HSLA) Steel

Abstract: The main goal of this study was to develop a new processing technology for a high-strength low-alloy (HSLA) steel in order to maximize the mechanical properties attainable at its low alloy levels. Samples of the steel were processed using thermal deformation schedules carried out in single-phase (γ) and dual-phase (γ + α) regions. The samples were rolled at unconventional finishing temperatures, their final mechanical properties were measured, and their strength and plasticity behavior was analyzed. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[1][2][3][4][5][6][7] This has been shown to occur throughout the austenite phase field. 8,9) In earlier publications, the present authors have reported that the amounts of ferrite formed per pass increase with decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This has been shown to occur throughout the austenite phase field. 8,9) In earlier publications, the present authors have reported that the amounts of ferrite formed per pass increase with decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“… plastic deformation conditions realized in monophase austenite region at deformation temperatures. spontaneous recrystallization of austenite—RCR [ 62 , 63 , 64 ] produced polycrystalline austenitic grains with diameter dγ ≈ 50–80 μm, which transformed to polycrystalline ferrite grain with diameter dα ≈10–30 μm, non-recrystallization austenite region—CR [ 56 , 63 ] (narrowly raised Ar3 temperature) formed deformation-elongated austenitic grains with an effective ferritic nucleation surface calculated from grain boundaries and deformation bands Sv(gb+db) ≈ 25–500 1/mm [ 56 ]. This corresponds to the corrected diameter grains of austenite d γ, cor ≈ 4–70 μm) transformed to polycrystalline ferrite with diameter d α ≈ 2–10 μm.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to the corrected diameter grains of austenite d γ, cor ≈ 4–70 μm) transformed to polycrystalline ferrite with diameter d α ≈ 2–10 μm. dual-phase (γ+α) region—CR [ 55 , 63 ] (non-recrystallized austenite–deformed ferrite) bellow Ar3 temperatures with Sv(gb+db) ≈1000 1/mm, corresponding to d γ, cor ≈ 2 μm with subsequent transformation to ferrite (non-recrystallized austenite, to polycrystalline ferrite–deformed ferrite, to ferrite subgrains) with diameter d α ≈ 1–2 μm. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations